2022
DOI: 10.3389/fbioe.2022.964397
|View full text |Cite
|
Sign up to set email alerts
|

The impact of serum-free culture on HEK293 cells: From the establishment of suspension and adherent serum-free adaptation cultures to the investigation of growth and metabolic profiles

Abstract: Serum-free cultures are preferred for application in clinical cell therapy and facilitate the purification processes of bioproducts, such as vaccines and recombinant proteins. It can replace traditional cell culture - eliminating potential issues posed by animal-derived serum supplementation, such as lot to lot variation and risks of pathogen infection from the host animal. However, adapting cells to serum-free conditions can be challenging and time-consuming, and is cell line and medium dependent. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…This is for 180 , for 275 , and for 350 . The values also reflect what is documented in the literature, where typical maximum specific growth rates for HEK293 cells range from 0.020 to 0.029 [ 23 , 24 , 25 , 26 ]. In order to follow the aggregate formation and cell morphology online, experiments were carried out using the iLine F probe.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This is for 180 , for 275 , and for 350 . The values also reflect what is documented in the literature, where typical maximum specific growth rates for HEK293 cells range from 0.020 to 0.029 [ 23 , 24 , 25 , 26 ]. In order to follow the aggregate formation and cell morphology online, experiments were carried out using the iLine F probe.…”
Section: Resultssupporting
confidence: 83%
“…A detailed analysis of different HEK293 cell lines can be found in the studies by Malm et al [ 19 ] and Tan et al [ 3 ]. HEK293 cells growing in suspension typically have mean cell diameters ranging from 14 to 16 [ 20 , 21 , 22 ] and a typical maximum specific growth rate ranging from 0.020 –0.029 [ 23 , 24 , 25 , 26 ]. Jang et al [ 24 ] were able to demonstrate comparable growth rates between adherent growing and in suspension growing HEK293 cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, the basal medium, HyCell TransFx‐H, which contains around 6 g L −1 (33.3 m m ) of glucose, was supplemented with either glucose or Cells Boost 5. The amount of supplement added was based on the cell‐specific consumption rate of glucose (average of 4.8 pmol cell −1 day −1 and similar to reported values [ 76 ] ) so that a minimum of 2 g L −1 (11.1 m m ) of glucose was available at any given time, [ 77 ] mimicking the observed glucose concentrations in the LCD productions. HEK293 cells exhibit a high level of glycolytic activity [ 78 ] and higher consumption rates have been associated with improved viral productions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cell culture-based viruses are more similar to the circulating strains than the viruses produced in eggs as hosts, which may contain antigenic variations . The human embryonic kidney (HEK) 293 cell lines have been commonly used over the last decades, not only for the basic research such as protein interaction and signal transduction studies but also for the GMP manufacturing of recombinant proteins and viral vectors in the biopharmaceutical industry owing to the high transfectivity, acceptable growth rate, and human-like post-translation modifications. For this cell line, the results showed that the host cell passage number, ratio of the number of virus particles to each cell (i.e., multiplicity of infection (MOI)), viable cell density (VCD), viral stock passage number, contact time of the adenoviral vector with the host cells during culture, and host cell viability during infection are all critical factors that affect a successful infection. ,, Previous studies have also declared that addition of fresh culture medium at the time of infection (ToI) or the feeding strategies (with glucose or amino acids) at 24 h post-infection (hpi) together with pH controlling within the optimal ranges allowed a high rAd productivity at VCD = 2–3 × 10 6 cells/mL. , …”
Section: Introductionmentioning
confidence: 99%